Conservation values of understory vascular plants in even- and uneven-aged Nothofagus antarctica forests - Martínez Pastur, Guillermo José; Rosas, Yamina Micaela; Cellini, Juan Manuel; Barrera, Marcelo Daniel; Toro Manríquez, Mónica D.R.; Huertas Herrera, Alejandro; Favoretti Bondar, Santiago; Lencinas, María Vanessa; Peri, Pablo Luis (Biodiversity and Conservation, 2020)
Usually, stands with aging trees are considered forests with higher conservation values, regardless their structural diversity and other functional attributes. Natural stands present a wide range of age structures, from even-aged stands growing at different development growth phases (e.g. CO = stands at initial or final optimum development growth phase, MD = stands at mature or decaying development growth phases) to uneven-aged stands with mixed development growth phases (e.g. UOG = stands combining mature or decaying development growth phases with initial or final optimum development growth phases, UMD = stands combining only mature and decaying development growth phases). The aim of this work was to compare richness and cover of understory vascular plants of even- and uneven-aged stands of Nothofagus antarctica (ñire) forests in Tierra del Fuego (Argentina), and relate these characteristics with abiotic, soil and forest structure variables. A total of 75 stands were sampled across the natural range distribution of the forests, where understory (point intercept method), forest structure (angle count sampling and eye-fish photos) and environmental (soil) variables were measured. 17 one-way ANOVAs were conducted using Tukey test at p < 0.05 to compare the means. Among forest structure and environmental variables, cover (F = 4.3, p = 0.007), radiation (F = 4.4, p = 0.006), phosphorous (F = 3.9, p = 0.012), tree density (F = 10.3, p < 0.001), tree diameter (F = 10.3, p < 0.001) and stand growth (F = 4.9, p = 0.004) showed significant differences, and in general with a positive or negative trend across the MD—UMD—UOG—CO gradient. Total (F = 6.5, p < 0.001) and native species richness of the understory (F = 7.2, p < 0.001) were significantly different among forest types, where UMD > UOG > MD > CO (17–28 total, and 13–24 native species, respectively). Neither exotic species richness (4–5 species) nor understory cover significantly changed among treatments (total, dicots, ferns and bryophytes). However, monocots cover significantly differed among treatments (F = 3.9, p = 0.012), where UMD > MD > UOG > CO. Finally, indicator species cover for environmental degradation did not present significant differences (F = 2.1, p = 0.106), but they were positive related to forests growing in mature stages. We concluded that uneven-aged stands presented significantly higher conservation values compared to even-aged stands, where mature/decay stands have better conservation values than optimum growth development phases. These findings can be used for better silviculture practices that combine silvopastoral use and conservation strategies. EEA Santa Cruz Fil: Martínez Pastur, Guillermo José. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas. Laboratorio de Recursos Agroforestales; Argentina Fil: Rosas, Yamina Micaela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas. Laboratorio de Recursos Agroforestales; Argentina Fil: Cellini, Juan Manuel. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. Laboratorio de Investigaciones en Maderas; Argentina Fil: Barrera, Marcelo Daniel. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. Laboratorio de Investigaciones en Maderas; Argentina Fil: Toro Manríquez, Mónica D.R. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas. Laboratorio de Recursos Agroforestales; Argentina Fil: Huertas Herrera, Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas. Laboratorio de Recursos Agroforestales; Argentina Fil: Favoretti Bondar, Santiago. Universidad Nacional de Tierra del Fuego. Instituto de Ciencias Polares, Ambiente y Recursos Naturales; Argentina Fil: Lencinas, María Vanessa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas. Laboratorio de Recursos Agroforestales; Argentina Fil: Peri, Pablo Luis. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Santa Cruz; Argentina. Universidad Nacional de la Patagonia Austral; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina